Producer's Role in Production Management of The Short Film “Piknik Panik” - Danang Prasetyo; Fajar Junaedi (Jogjakarta Communication Conference (JCC), 2023)
Filmmaking requires careful preparation and planning led by a producer. The producer's role is very important because it manages all activities from pre-production, and production, till post-production. The Piknik Panik film is a short fiction film produced by Umar Al Jufri who criticizes the existence of tour brokers in the community. Piknik Panik film has won the Best Acffest Movie Award Category Shot Fiction 2021. This research is a qualitative descriptive study with in-depth interviews and document studies in data collection. The results of the research show that the stages carried out by producers during pre-production include assembling a team, making a breakdown of scripts, making schedules, designing budgets, and managing actors. At the production stage, the producer performs his duties in terms of monitoring, controlling, and solving problems. The post-production stage is preparing editing needs, making timelines, reports, and film distribution. With the analysis that has been done, the role of the producer in the film Piknik Panik. There is a stage that is adjusted to the needs and conditions of production, namely the rehearsal process is eliminated because the producer maximizes scene blocking, tempo, and gestures during reading.